2006
DOI: 10.1099/ijs.0.64056-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomonas azotifigens sp. nov., a nitrogen-fixing bacterium isolated from the roots of Oryza sativa

Abstract: Three yellow-pigmented strains associated with rice plants were characterized by using a polyphasic approach. The nitrogen-fixing abilities of these strains were confirmed by acetylene reduction assay and nifH gene detection. The three strains were found to be very closely related, with 99?9 % 16S rRNA gene sequence similarity and greater than 70 % DNA-DNA hybridization values, suggesting that the three strains represent a single species. 16S rRNA gene sequence analysis indicated that the strains were closely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
51
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(54 citation statements)
references
References 24 publications
1
51
0
Order By: Relevance
“…The chemotaxonomic features of strain V2M44 T , including Q-10 as the major isoprenoid quinone, C 17 : 1 v6c and summed feature 7 as the major fatty acids, the absence of 3-hydroxy fatty acids and the presence of sphingoglycolipid are as expected for species closely related to the genus Sphingomonas (Busse et al, 2003;Denner et al, 1999Denner et al, , 2001Kämpfer et al, 1997;Lee et al, 2001;Reddy & Garcia-Pichel, 2007;Romanenko et al, 2007;Takeuchi et al, 1995;Xie & Yokota, 2006;Yoon et al, 2006). The DNA base composition was determined by thermal denaturation (Marmur & Doty, 1962) and Escherichia coli K-12 T was used as the reference.…”
Section: Cells Of Strain V2m44mentioning
confidence: 70%
See 1 more Smart Citation
“…The chemotaxonomic features of strain V2M44 T , including Q-10 as the major isoprenoid quinone, C 17 : 1 v6c and summed feature 7 as the major fatty acids, the absence of 3-hydroxy fatty acids and the presence of sphingoglycolipid are as expected for species closely related to the genus Sphingomonas (Busse et al, 2003;Denner et al, 1999Denner et al, , 2001Kämpfer et al, 1997;Lee et al, 2001;Reddy & Garcia-Pichel, 2007;Romanenko et al, 2007;Takeuchi et al, 1995;Xie & Yokota, 2006;Yoon et al, 2006). The DNA base composition was determined by thermal denaturation (Marmur & Doty, 1962) and Escherichia coli K-12 T was used as the reference.…”
Section: Cells Of Strain V2m44mentioning
confidence: 70%
“…T from related members of the genus Sphingomonas Taxa: 1, V2M44 T ; 2, S. mali NBRC 15500 T (data from Takeuchi et al, 1995); 3, S. kaistensis PB56 T (Kim et al, 2007); 4, S. oligophenolica S213 T (Ohta et al, 2004); 5, S. dokdonensis DS-4 T (Yoon et al, 2006); 6, S. pituitosa EDIV T (Denner et al, 2001); 7, S. pruni NBRC 15498 T (Takeuchi et al, 1995); 8, S. aerolata NW12 T (Busse et al, 2003); 9, S. asaccharolytica NBRC 15499 T (Takeuchi et al, 1995); 10, S. azotifigens Y39 T (Xie & Yokota, 2006 nidase, a-galactosidase, b-galactosidase, b-glucuronidase, b-glucosidase, a-glucosidase, a-mannosidase and a-fucosidase activities are absent. The predominant cellular fatty acids are C 17 : 1 v6c, summed feature 7 (comprising C 18 : 1 v7c, C 18 : 1 v9t and/or C 18 : 1 v12t), C 16 : 0 , C 17 : 1 v8c and C 15 : 0 2-OH.…”
Section: Cells Of Strain V2m44mentioning
confidence: 99%
“…Although the polar lipids of the type strains of both Sphingomonas echinoides and Sphingomonas oligophenolica have been analysed Ohta et al, 2004) For polyamine analysis, strain C16y T was grown in PYE medium (containing 0.3 % yeast extract, 0.3 % peptone; pH 7) at 20 u C. Polyamines were extracted as described by Busse & Auling (1988) and analysed as described by Busse et al (1997) ] sym-homospermidine (38.9), spermidine (13.0), spermine (3.4), 1,3-diaminopropane (1.6) and putrescine (0.5). The presence of symhomospermidine as a major compound in the polyamine pattern has been considered as a diagnostic feature of the genus Sphingomonas Takeuchi et al, 2001), and species recently assigned to this genus also share this trait (Busse et al, 2003(Busse et al, , 2005Xie & Yokota, 2006; Kämpfer et al, 2007; Huang et al, 2009;Roh et al, 2009;Nigam et al, 2010;Zhang et al, 2010). However, it has been reported that species of the related genus Sphingosinicella also contain sym-homospermidine as the major compound (Geueke et al, 2007) in the polyamine pattern, which hampers the classification of novel strains within this family.…”
Section: Sphingomonas Echinoides Dsm 1805mentioning
confidence: 99%
“…Currently, more than 30 species with validly published names in the genus Sphingomonas sensu stricto have been isolated from various environments, including natural mineral water (Lee et al, 2001), plants (Takeuchi et al, 1995;Xie & Yokota, 2006) and soil (Ohta et al, 2004;Reddy & Garcia-Pichel, 2007;Yoon et al, 2006).…”
mentioning
confidence: 99%